Pictorial Health Warning and Intention to Quit Smoking in Smokers in an Urban Campus Jakarta - Sarah Handayani; Elia Nur A'yunin; Rifdah Amalia (Universitas Airlangga, 2024)
Background: Research on eye-tracking among active smokers shows they avoid the health warnings on cigarette packages, which still occur even without prominent imaging information. Aims: To evaluate the reactions and perceptions to pictorial health warning (PHW) labels by measuring eye-tracking devices and knowing their relationship to smoking cessation intention. Methods: The study used a cross-sectional design with measurements of PHW on cigarette packs by eye-tracker tools of type Tobii-data collection. With a non-random sampling technique, 50 respondents were from civitas academics on Campus-A UHAMKA. Samples were selected based on inclusion criteria: men, active smokers, not colorblind, and who didn't intend to stop smoking three months before the study. Results: The number also shows that most respondents already have strong intentions. The majority of respondents (64%) want to improve their health. However, 20% of those surveyed have no reason to quit smoking. That might represent the respondent's low intention to quit smoking. A bivariate test showed no significant association between respondents' attitudes toward smoking cessation intention (p-value: 0.706) and subjective norms for smoking cessation intention (p-value: 0.706). The eye-tracking results found that the different gaze plots and heatmap results on cigarette packets showing smoking-related diseases were more directed to the PHW area of interest. However, on smoking behavior images, the gaze plot and heatmap showed scattered results for PHW and cigarette brands. Conclusion: Although it has not been proven significantly related to smoking cessation intention, PHW has been the respondents' focus. We need further research on the shape and size of PHW.